Low-dose IL-2 improved clinical symptoms by restoring reduced regulatory T cells in patients with refractory rheumatoid arthritis: A randomized controlled trial - Wang, Jia; Zhang, Sheng-Xiao; Chang, Jia-Song; Cheng, Ting; Jiang, Xiao-Jing; Su, Qin-Yi; Zhang, Jia-Qi; Luo, Jing; Li, Xiao-Feng (Frontiers in Immunology, 2022)
BACKGROUND Regulatory T cells (Tregs) have been found to play crucial roles in immune tolerance. However, the status of Tregs in refractory RA is still unclear. Moreover, low-dose interleukin-2 (IL-2) has been reported to selectively promote the expansion of Tregs. This study investigated the status of CD4+Tregs and low-dose IL-2 therapy in patients with refractory RA. METHODS Absolute number of CD4+CD25+FOXP3+ Treg (CD4Treg), CD4+IL17+ T (Th17), and other subsets in Peripheral blood (PB) from 41 patients with refractory RA and 40 healthy donors were characterized by flow cytometry combined with an internal microsphere counting standard. Twenty-six patients with refractory RA were treated with daily subcutaneous injections of 0.5 million IU of human IL-2 for five consecutive days. Then its effects on CD4Treg and Th17 cells in PB were analyzed. RESULTS A decrease in the absolute number of PB CD4Tregs rather than the increase in the number of Th17 was found to contribute to an imbalance between Th17 and CD4Tregs in these patients, suggesting an essential role of CD4Tregs in sustained high disease activity. Low-dose IL-2 selectively increased the number of CD4Tregs and re-balanced the ratio of Th17 and CD4Tregs, leading to increased clinic symptom remission without observed side effects. CONCLUSIONS Absolute decrease of PB CD4Tregs in patients with refractory RA was associated with continuing disease activation but not the increase of Th17 cells. Low-dose IL-2, a potential therapeutic candidate, restored decreased CD4Tregs and promoted rapid remission of patients with refractory RA without over-treatment and evaluated side effects.